Patient management for thoracic organ donor candidates: the lung transplantation team’s view - Hye Ju Yeo (Clinical Transplantation and Research, 2024)
Despite the increasing demand for lung transplants, donor lungs remain in short supply. Although organ donations have been steadily increasing in Korea, with the utilization rate for donor lungs increasing to 40% in recent years, many potential donor organs remain unused. To match the increasing number of patients on the lung transplant waitlist, it is essential to increase the donor procurement rate through optimal management. Improvements in donor lung management programs can lead to expansion of the donor pool and optimal posttransplant outcomes. This review focuses on basic protocols for the optimal management of donor lungs and summarizes coronavirus disease 2019-related considerations for donor lung evaluation.